PERANCANGAN APLIKASI PENJUALAN BERBASIS WEB PADA TOKO JAYA BERNAH DALAM - Rini Wahyuni; Adi Wibowo; Susilo Hartono (LPPM Universitas Muhammadiyah Kotabumi, 2023)
Online shop websites are currently increasingly developing, with online shop websites making it easier for buyers and sellers to see the goods being sold anywhere and at any time and sellers can promote the goods they sell to the wider public. The aim of creating this website is to help the Jaya grocery store to be able to check online and manage the stock of basic food items and also avoid several errors that can occur such as errors in inputting quantities and prices. It is hoped that by designing this web-based sales application it can help grocery stores successful in increasing sales and expanding the marketing process in online and offline forms. The process of designing this application uses the prototype method for making this website with the aim that the final process of this design can then be used according to the needs of the Jaya grocery store. Currently we are entering technological progress which is increasing day by day, because this development covers several aspects, even all aspects involving human life. With the development of this technology, this technology is not only used as a communication medium but also to expand the business network of business actors. one of these business actors is the Jaya grocery store, in order to be able to compete healthily in the global world, it needs a tool or something that can be used to reach the market as expected, in this case, namely to improve its business or to increase its sales scope. The purpose of this research is to be able to design an information system for ordering goods online or on a web basis, how to help the Jaya grocery store to increase sales volume and further expand the marketing process in online and offline forms.